Army Film and the Avant Garde : Cinema and Experiment in the Czechoslovak Military - Lovejoy, Alice (Book collections on Project MUSE., 2014)
During the 1968 Prague Spring and the Soviet-led invasion and occupation that followed, Czechoslovakia's Army Film studio was responsible for some of the most politically subversive and aesthetically innovative films of the period. Although the studio is remembered primarily as a producer of propaganda and training films, some notable New Wave directors began their careers there, making films that considerably enrich the history of that movement. Alice Lovejoy examines the institutional and governmental roots of postwar Czechoslovak cinema and provides evidence that links the Army Film studio to Czechoslovakia's art cinema. By tracing the studio's unique institutional dimensions and production culture, Lovejoy explores the ways in which the "military avant-garde" engaged in dialogue with a range of global film practices and cultures